Life Design Counseling: Theory, Methodology, Challenges, and Future Trends - Wen, Ya; Li, Kai; Chen, Huaruo; Liu, Fei (Frontiers in Psychology, 2022)
COVID-19 has become a global pandemic, accelerating economic recession and large-scale unemployment, previous career counseling focusing on personal choice has been difficult to meet individuals' needs. It is very meaningful and valuable to introduce the ideology of Life Design Counseling. In this mini review, we introduce and analyze the theory and methodology of Life Design Counseling. This review puts forward challenges in the field of Life Design Counseling, including the lack of applicability and diversity of theory, the lack of attention to clients from multiple backgrounds, and the lack of diversified research. The theoretical research, practical research, and the integration of theory and practice of Life Design Counseling still need to be further concerned by researchers.